The use of titanium (IV) phosphate for metal removal from aqueous and alcoholic samples - Pipi, Angelo R. F. [UNESP]; Aquino Neto, Sidney; Pereira Barbosa, Priscila Fernanda [UNESP]; Do Carmo, Devaney R. [UNESP] (Springer, 2019)
Adsorption methods are widely employed for the removal of metals from aqueous medium, being an efficient and environmentally friendly technique for wastewater treatment. From the several adsorptive materials that are being employed by the specialized literature in removal processes, TiO2 continues to be a wise choice. In this work, we have prepared a phosphate-modified TiO2 (TiPh) and tested their adsorptive behavior toward different metallic species. TiPh synthesis was carried out from a titanium (IV) isopropoxide in aqueous phosphoric acid solution. The adsorption of Co+2, Cu+2, and Ni+2 in a TiPh matrix was investigated in different media: water, 42% ethanol aqueous solution, and pure ethanol. The kinetic assays results indicated that the adsorption equilibrium occurs after 10-40 min, being higher for alcoholic solutions. The higher capacity values were obtained in the 42% ethanol aqueous solution, in which N-f values of 9.1 x 10(-4) mol g(-1), 5.9 x 10(-4) mol g(-1), and 5.1 x 10(-4) mol g(-1) were obtained for Cu+2, Co+2, and Ni+2, respectively.
Keywords: Adsorption; Composite; Titanium phosphate; Metal ions; Langmuir adsorption model